Analysis of Patchouli Oil Processing (Patchouli Oil) and Business Feasibility in Wandoke Village Tiworo District West Muna Islands - sahrul, ade; Karimuna, La; Herdhiansyah, Dhian (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2020)
This study aims to determine patchouli oil processing and the feasibility of patchouli oil processing business in Wandoke Village, Tiworo Islands District, West Muna Regency. The analytical method used in this study is qualitative and quantitative methods, qualitative methods are used to describe patchouli oil processing, while the quantitative method is used to analyze the feasibility of the patchouli oil processing business using the Revenue Cost Ratio (R / C) formula. The results of the study showed that the patchouli oil processing process used in Wandoke Village, Tiworo Islands Subdistrict, West Muna Regency through a distillation process. Distillation used is by distillation of water and steam, in the process of distillation of water and steam through a kettle filled with water to the sieve limit and patchouli leaves on the filter then the water is boiled and produces steam which will pass through the material and flow through stainless pipes. The results of the analysis of the feasibility of the patchouli oil processing business are based on the RC rato analysis of 1.34. This shows that 1.34 R / C> 1, shows that every rupiah value spent in the production of patchouli oil will provide benefits and feasible to be developed. So it can be concluded that the processing of patchouli oil in Wandoke Village, Tiworo Islands District, West Muna Regency through and water steam distillation system, and patchouli oil processing business in Wandoke Village, Tiworo Islands Subdistrict, West Muna Regency is feasible to cultivate.